PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) IPAS BERBASIS PRAKTIKUM SEDERHANA BAGI SISWA KELAS IV SD - Dhena, Gervarsia Virjinlia Anita; Kua, Maria Yuliana; Dolo, Fransiskus Xaverius; Ngurah Laba Laksana, Dek (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The lack of innovation from teachers in creating learning materials in the 5.0 era significantly impacts overall learning standards. Student Worksheets (LKPD) are essential learning materials for students, especially those focusing on practicum. The use of practicum-based LKPD is still lacking at UPTD SDI Tarawaja. This research aims to create a simple Student Worksheet (LKPD) using a practical approach, especially for Natural and Social Sciences (IPAS) subjects. This research uses a Research and Development (R&D) approach by applying the 3D development model (Define, Design, and Develop). The research was carried out at UPTD SDI Tarawaja, Soa District, Ngada Regency, East Nusa Tenggara Province involving 5 grade IV students and 1 teacher. Data analysis was carried out on a limited basis by material experts, design experts, and language experts, all science teachers. The data includes quantitative data from validation results by experts, responses from students and teachers via questionnaires, and qualitative data obtained through suggestions and input from assessors. The percentage of validation by material experts reached 90%, design experts reached 87%, and language experts reached 82%. Responses from teachers via questionnaire reached 90.7%, while responses from students reached 88%. The findings from the research show that the LKPD that has been developed has a high level of validity and is very suitable for use in science and science learning in fourth-grade elementary school.